2022
DOI: 10.1007/s10067-022-06183-2
|View full text |Cite
|
Sign up to set email alerts
|

Validity and reliability of the Arabic version of the Self-Efficacy for Managing Chronic Disease scale in rheumatoid arthritis patients

Abstract: Background and objectives Rheumatoid arthritis (RA) is an autoimmune inflammatory condition that causing disability and affection of patient’s quality of life (QoL). Self-efficacy investigation helps us to detect the requirements of chronically affected patients and evaluation of self-care management programs. The aim of our study was to test validity and reliability of Self-Efficacy for Managing Chronic Disease (SEMCD-Arabic) in RA patients. Method This s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 20 publications
1
2
0
Order By: Relevance
“…There were no differences in the self-efficacy for the management of chronic disease of the participants analyzed in this study, except when this construct was compared in relation to academic level, in which 52% of the sample completed elementary school and 24% completed secondary school, see Table 4 , which coincides with the research conducted in Chile where a relationship was found between educational level and adherence to treatment in patients with chronic diseases and stress [ 32 ], while educational schooling is not related to self-efficacy [ 19 , 21 , 24 ].…”
Section: Discussionsupporting
confidence: 69%
See 2 more Smart Citations
“…There were no differences in the self-efficacy for the management of chronic disease of the participants analyzed in this study, except when this construct was compared in relation to academic level, in which 52% of the sample completed elementary school and 24% completed secondary school, see Table 4 , which coincides with the research conducted in Chile where a relationship was found between educational level and adherence to treatment in patients with chronic diseases and stress [ 32 ], while educational schooling is not related to self-efficacy [ 19 , 21 , 24 ].…”
Section: Discussionsupporting
confidence: 69%
“…In contrast to this characteristic, in the rest of the sociodemographic aspects the means of the latent factors were similar, different from studies conducted in Europe and Asia where age and gender marked a significant difference in self-efficacy against the disease and quality of life of patients. [ 19 , 24 ]; in this case, the results suggest that people who completed high school or university studies showed higher self-efficacy than those who reached primary school levels, which implies a statistically significant difference of low magnitude (Dif.=0.38, z = 2.33, p = .020, Cohen’s d = 0.32).…”
Section: Discussionmentioning
confidence: 85%
See 1 more Smart Citation